DAKWAH DI ERA MODERN (Tinjauan Tafsir terhadap Ayat tentang Dakwah Nabi Musa as. kepada Fir’aun dalam QS T̩a̅ha̅/20 : 42-44) - Abdurrahman (Jurnal Dakwah Tabligh, 2022)
Religious teachings originating from the Qur'an will certainly be increasingly accepted by mankind if the delivery method is appropriate, as did the Prophet Musa to his people, especially to Pharaoh in QS Taha/20: 42–44. Regardless of the results of the prophet's da'wah Moses to Pharaoh, the method used should be an example for the preachers in modern era, some of which are colored with hate speech, insults, and fake news. This paper is expressed descriptively and qualitatively by explaining the verse in tahlili to know in depth the correct and appropriate way of da'wah, such as the method used by the Prophet Moses, namely by using qaulan layyina̅, meaning the da'wah delivered by the prophet Moses. gently, but that does not mean that it seems to weaken the preacher. qaulan layyina̅ can be interpreted as a gentle da'wah, with a pleasant voice, a good attitude, and pleasant behavior.